Characterization and Antibacterial Activity of Biosynthesized Zinc Oxide–Silver (ZnO–Ag) Nanocomposites Using Manihot esculenta Leaf Extract (Biosaintifika: Journal of Biology & Biology Education, 2026)
Pseudomonas aeruginosa, an important opportunistic pathogen responsible for nosocomial infections, poses a threat in clinical care. Metal-metal oxide nanocomposites have been developed as antibacterial agents due to their synergistic effects. In this study, zinc oxide-silver nanocomposites (ZnO–AgNCs) were synthesized using Manihot esculenta leaf extract as a bioreductant, with extract concentrations of 5%, 10%, and 15% (v/v) and AgNO₃ concentrations of 6 and 8 mM. The samples were characterized using UV-Vis spectrophotometry, PSA, SEM-EDX, and their antibacterial activity was tested using the disk diffusion method. The best formulation was obtained for ZnO–AgNCs with 5% extract + 8 mM AgNO₃, which exhibited an SPR peak at 331 nm and an average particle size of 48.04 nm. SEM-EDX revealed an irregular and agglomerated morphology and confirmed the presence of Zn, O, and Ag. The nanocomposite showed strong antibacterial activity against P. aeruginosa with an inhibition zone of 15.83±0.64 mm. These findings highlight its potential for further development in infection control, particularly in medical applications. This study supports the Sustainable Development Goal (SDGs) on Good Health and Well-being (No. 3) through the development of antibacterial materials.